An evaluation of pharmacist knowledge on treatment with antiepileptic drugs. (January 2016) - Roth, Yifat; Neufeld, Miri Y.; Blatt, Ilan; Guy-Alfandary, Shiri; Rasaby, Sivan; Ekstein, Dana; Eyal, Sara
Highlights: Pharmacists are knowledgeable regarding several aspects of epilepsy care. Knowledge is related to PharmD degree and to shorter duration since training. 12% identified correctly all situations requiring urgent physician consultation. The findings indicate the need for improving pharmacists' education regarding epilepsy. Abstract: Purpose: As pharmacists play an important role in managing antiepileptic drug (AED) therapy, they should be aware of different aspects of the treatment. Our aim was to evaluate pharmacists' knowledge of the pharmacological treatment of epilepsy, and their recommendations under hypothetical situations, through a written questionnaire. Methods: The questionnaire included 22 questions divided into three sections: demographic data (eight questions), knowledge of specific aspects of AED therapy (true/false; four questions), and actions taken in theoretical situations involving AED therapy (multiple choice; ten questions). The questionnaire was distributed to pharmacists practicing in Israel and working in pharmacies and/or participating in professional meetings and continued education programs. Results: One hundred and twenty one pharmacists completed the questionnaire (response rate 19%). The mean overall score was 48 ± 15% correct answers. Most pharmacists were aware of the need to continue AED treatment during pregnancy, the risk of generic switches, and the need to call the physician for loss of seizure control (92%, 89% and 81% of responders, respectively). Twelve percent identified correctly all three situations in which the clinicians should be contacted urgently, and 27% did not identify any of them. The total score was related to the academic degree (PharmD vs. other) and to the duration since training completion. Conclusion: Pharmacists were knowledgeable regarding some aspects of care of people with epilepsy. However, our study, as in previous studies among health care professionals, identified some gaps in knowledge. These findings indicate the need for better education of pharmacists regarding epilepsy and its treatment.